Deregulated expression of the imprinted DLK1-DIO3 region in glioblastoma stemlike cells: tumor suppressor role of lncRNA MEG3. Issue 12 (27th May 2020) - Buccarelli, Mariachiara; Lulli, Valentina; Giuliani, Alessandro; Signore, Michele; Martini, Maurizio; D'Alessandris, Quintino G; Giannetti, Stefano; Novelli, Agnese; Ilari, Ramona; Giurato, Giorgio; Boe, Alessandra; Castellani, Giorgia; et al.
Abstract: Background: Glioblastoma (GBM) stemlike cells (GSCs) are thought to be responsible for the maintenance and aggressiveness of GBM, the most common primary brain tumor in adults. This study aims at elucidating the involvement of deregulations within the imprinted delta-like homolog 1 gene‒type III iodothyronine deiodinase gene ( DLK-DIO3 ) region on chromosome 14q32 in GBM pathogenesis. Methods: Real-time PCR analyses were performed on GSCs and GBM tissues. Methylation analyses, gene expression, and reverse-phase protein array profiles were used to investigate the tumor suppressor function of the maternally expressed 3 gene (MEG3). Results: Loss of expression of genes and noncoding RNAs within the DLK1-DIO3 region was observed in GSCs and GBM tissues compared with normal brain. This downregulation is mainly mediated by epigenetic silencing. Kaplan–Meier analysis indicated that low expression of MEG3 and MEG8 long noncoding (lnc)RNAs significantly correlated with short survival in GBM patients. MEG3 restoration impairs tumorigenic abilities of GSCs in vitro by inhibiting cell growth, migration, and colony formation and decreases in vivo tumor growth, reducing infiltrative growth. These effects were associated with modulation of genes involved in cell adhesion and epithelial-to-mesenchymal transition (EMT). Conclusion: In GBM, MEG3 acts as a tumor suppressor mainly regulating cell adhesion, EMT, and cell proliferation, thus providing a potential candidate for novel GBM therapies.